2000
DOI: 10.1109/58.818764
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the longitudinal vibration system for the hybrid transducer ultrasonic motor

Abstract: This paper presents a symmetric hybrid transducer ultrasonic motor designed to produce large longitudinal vibration stress in the rotor/stator contact interface for high-torque operation. The nodal plane of the longitudinal vibration mode was adjusted to match the rotor/stator contact interface, and the piezoelectric ceramic disks for the longitudinal vibration were installed at the nodal plane of the longitudinal vibration mode for effective excitation. An experimental motor, 20 mm in diameter, using the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…A symmetric hybrid transducer ultrasonic motor developed by Tomikawa et al [4], [5] has two rotors that sandwich the stator. The authors reported excellent performance in a symmetric design prototype with output from two rotors transmitted through a common driveshaft extending through the center of a hollow stator [6]. However, a comparison of the symmetric design with the traditional asymmetric designs that produce their output from one only rotor has not been performed in detail.…”
Section: Introductionmentioning
confidence: 89%
“…A symmetric hybrid transducer ultrasonic motor developed by Tomikawa et al [4], [5] has two rotors that sandwich the stator. The authors reported excellent performance in a symmetric design prototype with output from two rotors transmitted through a common driveshaft extending through the center of a hollow stator [6]. However, a comparison of the symmetric design with the traditional asymmetric designs that produce their output from one only rotor has not been performed in detail.…”
Section: Introductionmentioning
confidence: 89%
“…Researchers have developed various types of USM over the past four decades. Existing designs generally fall into several geometric types of piezoceramic ultrasonic actuators: ring-type [7,8], cylinder-type [9][10][11], disk-type [12][13][14][15][16], hollow cylindertype [17][18][19][20][21], etc. Most studies on this topic focus on the steady state response and performance, and relatively few researchers have investigated the transient response of the USM.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve such motor, several methods to matching the resonance frequencies of longitudinal and torsional vibrations have been proposed in Refs. [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%